SEPAK BOLA DAN PERGERAKAN KAUM BUMIPUTRA DI BANDUNG, 1900-1940 - Angga Pusaka Hidayat (Universitas Sultan Ageng Tirtayasa, 2022)
This paper intends to show the connection between sport and the natives movement in a colonized society that was built on differences in social status and skin color. Sport, especially football, has become a tool used to carry out socio-political movements. The biggest influence that football shows is its ability to be used in large numbers. In seeing football as a means of struggle, Bandung is used as a historical stage because this city is one of the centers of the national movement. The research method used is the historical method which includes the stages of finding and collecting sources, source criticism, interpretation, and presenting research representations in the form of historiography. The action approach is used as an analytical tool. This paper proposes the assumption that the bumiputra (natives) play football, which can be interpreted as an attempt to change the order of colonial society. Bumiputera playing football is a way to show social equality with Europeans living in the Dutch East Indies. The movement of the football club’s in mobilizing the masses has encouraged Europeans and the colonial government in Bandung to choose to lower their aspirations. As a result, the colonial community structure became looser and the natives had the opportunity to associate with other social groups